Expertise, structured professional judgement and risk assessment - Davoren, Mary (Seminars in forensic psychiatry, 2024)
No-one can predict the future with accuracy. Yet doctors in all disciplines are required to make projections about the future and doctors are held to a level of expertise when exercising professional judgement within their scope of practice. The acquisition of expertise requires a knowledge of what expertise is in itself. Diagnosis is such a skill, demonstrating that unstructured professional judgement seldom exists in the absence of semi-structured or structured approaches to expert judgement. Risk has been taken as a paradigm for structured professional judgement. A thorough understanding of the nature of expertise in psychiatry and in the courts is necessary for the practice of forensic psychiatry. The process of both teaching and acquiring clinical expertise is considered both from first principles and in relation to topics such as the use of structured professional judgement instruments and judgement support frameworks. These extend to all aspects of practice including triage and needs assessment, leave, conditional discharge, treatment programme completion, forensic recovery, a range of functional mental capacities, legal defences and reliability.